Question 1 of 5Perform each Indicated Operation
Select the Correct Answer Below: Correct! Not Correct!
A
$$f(-1)=-1,f(3)=13,f(5)=20$$ $$f(-1)=-1$$$$f(3)=13$$$$f(5)=20$$
B
$$f(-1)=-4,f(3)=16,f(5)=50$$ $$f(-1)=-4$$$$f(3)=16$$$$f(5)=50$$
C
$$f(-1)=-12,f(3)=22,f(5)=35$$ $$f(-1)=-12$$$$f(3)=22$$$$f(5)=35$$
D
$$f(-1)=-1,f(3)=14,f(5)=90$$ $$f(-1)=-1$$$$f(3)=14$$$$f(5)=90$$
E
$$f(-1)=-10,f(3)=35,f(5)=105$$ $$f(-1)=-10$$$$f(3)=35$$$$f(5)=105$$
Question 2 of 5Perform each Indicated Operation
Select the Correct Answer Below: Correct! Not Correct!
A
$$f(-1)=-25,f(3)=500,f(5)=32,\hspace{-.15em}005$$ $$f(-1)=-25$$$$f(3)=500$$$$f(5)=32,\hspace{-.15em}005$$
B
$$f(-1)=-15,f(3)=300,f(5)=12,\hspace{-.15em}020$$ $$f(-1)=-15$$$$f(3)=300$$$$f(5)=12,\hspace{-.15em}020$$
C
$$f(-1)=-30,f(3)=255,f(5)=28,\hspace{-.15em}112$$ $$f(-1)=-30$$$$f(3)=255$$$$f(5)=28,\hspace{-.15em}112$$
D
$$f(-1)=-2,f(3)=100,f(5)=1002$$ $$f(-1)=-2$$$$f(3)=100$$$$f(5)=1002$$
E
$$f(-1)=6,f(3)=130,f(5)=588$$ $$f(-1)=6$$$$f(3)=130$$$$f(5)=588$$
Question 3 of 5Perform each Indicated Operation
Select the Correct Answer Below: Correct! Not Correct!
A
$$f(x+1)=-9x^2-2x-1$$$$f(x-1)=-9x^2+5x-1$$$$f(x+3)=12x^2-5x+1$$ $$f(x+1)=$$$$-9x^2-2x-1$$$$f(x-1)=$$$$-9x^2+5x-1$$$$f(x+3)=$$$$12x^2-5x+1$$
B
$$f(x+1)=x^2+3x+7$$$$f(x-1)=x^2+7x+21$$$$f(x+3)=20x^2-15x-35$$ $$f(x+1)=$$$$x^2+3x+7$$$$f(x-1)=$$$$x^2+7x+21$$$$f(x+3)=$$$$20x^2-15x-35$$
C
$$f(x+1)=7x^2-11x-18$$$$f(x-1)=9x^2+15x+14$$$$f(x+3)=20x^2+7x+14$$ $$f(x+1)=$$$$7x^2-11x-18$$$$f(x-1)=$$$$9x^2+15x+14$$$$f(x+3)=$$$$20x^2+7x+14$$
D
$$f(x+1)=-x^2-6x-13$$$$f(x-1)=5x^2+3x+21$$$$f(x+3)=22x^2-x-19$$ $$f(x+1)=$$$$-x^2-6x-13$$$$f(x-1)=$$$$5x^2+3x+21$$$$f(x+3)=$$$$22x^2-x-19$$
E
$$f(x+1)=-3x^2-4x-8$$$$f(x-1)=-3x^2+8x-12$$$$f(x+3)=-3x^2-16x-28$$ $$f(x+1)=$$$$-3x^2-4x-8$$$$f(x-1)=$$$$-3x^2+8x-12$$$$f(x+3)=$$$$-3x^2-16x-28$$
Question 4 of 5Perform each Indicated Operation
Select the Correct Answer Below: Correct! Not Correct!
A
$$f(x+7)=\frac{x-11}{3}$$$$f(x-z)=\frac{x^2+z}{3}$$$$f(x^2+z)=\frac{x^4+z^2+2}{3}$$ $$f(x+7)=$$$$\frac{x-11}{3}$$$$f(x-z)=$$$$\frac{x^2+z}{3}$$$$f(x^2+z)=$$$$\frac{x^4+z^2+2}{3}$$
B
$$f(x+7)=\frac{x+11}{2}$$$$f(x-z)=\frac{x-z+4}{2}$$$$f(x^2+z)=\frac{x^2+z+4}{2}$$ $$f(x+7)=$$$$\frac{x+11}{2}$$$$f(x-z)=$$$$\frac{x-z+4}{2}$$$$f(x^2+z)=$$$$\frac{x^2+z+4}{2}$$
C
$$f(x+7)=\frac{x-5}{5}$$$$f(x-z)=\frac{x-z+1}{5}$$$$f(x^2+z)=\frac{x^2-z-2}{5}$$ $$f(x+7)=$$$$\frac{x-5}{5}$$$$f(x-z)=$$$$\frac{x-z+1}{5}$$$$f(x^2+z)=$$$$\frac{x^2-z-2}{5}$$
D
$$f(x+7)=\frac{x^2+9}{2}$$$$f(x-z)=\frac{x^2+4}{2}$$$$f(x^2+z)=\frac{x^4+z^2+4}{2}$$ $$f(x+7)=$$$$\frac{x^2+9}{2}$$$$f(x-z)=$$$$\frac{x^2+4}{2}$$$$f(x^2+z)=$$$$\frac{x^4+z^2+4}{2}$$
E
$$f(x+7)=\frac{x^2+1}{3}$$$$f(x-z)=\frac{x^2-z^2+8}{3}$$$$f(x^2+z)=\frac{x^3+z^2+1}{3}$$ $$f(x+7)=$$$$\frac{x^2+1}{3}$$$$f(x-z)=$$$$\frac{x^2-z^2+8}{3}$$$$f(x^2+z)=$$$$\frac{x^3+z^2+1}{3}$$
Question 5 of 5Perform each Indicated Operation
Select the Correct Answer Below: Correct! Not Correct!
A
$$f(z+5)=z^4+z^2+2$$$$f(z^2+7)=2z^6+3z^3+2z$$$$f(z^2-3c)=3z^5-12c^2z^2+9c+1$$ $$f(z+5)=$$$$z^4+z^2+2$$$$f(z^2+7)=$$$$2z^6+3z^3+2z$$$$f(z^2-3c)=$$$$3z^5-12c^2z^2\hspace{.25em}+$$$$9c+1$$
B
$$f(z+5)=3z^2+30z+82$$$$f(z^2+7)=3z^4+42z^2+154$$$$f(z^2-3c)=3z^4-18cz^2+27c^2+7$$ $$f(z+5)=$$$$3z^2+30z+82$$$$f(z^2+7)=$$$$3z^4+42z^2+154$$$$f(z^2-3c)=$$$$3z^4-18cz^2+$$$$27c^2+7$$
C
$$f(z+5)=5z^2+15z+5$$$$f(z^2+7)=11z^4+12z^2+82$$$$f(z^2-3c)=3z^4-9cz^2+3c^2+c$$ $$f(z+5)=$$$$5z^2+15z+5$$$$f(z^2+7)=$$$$11z^4+12z^2+82$$$$f(z^2-3c)=$$$$3z^4-9cz^2\hspace{.25em}+$$$$3c^2+c$$
D
$$f(z+5)=12z^3+10z^2+4z$$$$f(z^2+7)=5z^5+18z^2-11$$$$f(z^2-3c)=12z^6-32c^2z+27z+1$$ $$f(z+5)=$$$$12z^3+10z^2+4z$$$$f(z^2+7)=$$$$5z^5+18z^2-11$$$$f(z^2-3c)=$$$$12z^6-32c^2z\hspace{.25em}+$$$$27z+1$$
E
$$f(z+5)=-z^3-2z^2+14$$$$f(z^2+7)=10z^3+12z^3-19z$$$$f(z^2-3c)=-11z^3-18z^2+81z+c$$ $$f(z+5)=$$$$-z^3-2z^2+14$$$$f(z^2+7)=$$$$10z^3+12z^3-19z$$$$f(z^2-3c)=$$$$-11z^3-18z^2\hspace{.25em}+$$$$81z+c$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »